More Than Human Dialoguess: Review of Julian Yates, Of Sheep, Oranges, and Yeast: A Multispecies Impression - Wallen, Martin (Humanimalia, 2018)
Julian Yates, Of Sheep, Oranges, and Yeast: A Multispecies Impression. Posthumanities. Minneapolis: University of Minnesota Press, 2017. 368 pp. $120 hc, $30 pb.